Pengembangan Rencana Pelaksanaan Pembelajaran (RPP) Menggunakan Model Pembelajaran Role Playing Pada Pembelajaran Tematik Di Kelas IV SDN Kota Bengkulu - Fitri Ramadayanti; Wurjinem Wurjinem; Sri Ken Kustianti (JURIDIKDAS, 2021)
This study aims to produce a Learning Implementation Plan (RPP) using a role playing learning model in grade IV Elementary School (SD) which can be used as a reference for teachers in implementing classroom learning. This study is a Research and Development (R&D) research by modifying the 4-D model. However, this research was only carried out until the third stage, namely Develop (Development). Validation is carried out by learning design experts and learning material experts. The lesson plans developed were given scores and responses by 8 public elementary school teachers in Bengkulu City. The data analysis technique used descriptive statistical analysis of the results of expert validation assessments and teacher responses as well as qualitative descriptive analysis of comments from expert validation and teacher responses. This study produced a Learning Implementation Plan (RPP) model using a role playing learning model with assessments from instructional design experts, learning materials and language on RPP validation of 94.6 with very good categories. The teacher's response was 91 with very good category. So, the research that has been carried out can be concluded that the lesson plan using the role playing learning model in thematic learning in grade IV SD can be categorized as a very good lesson plan and can be used in learning at school.Keywords: RPP, Development, Role Playing, Thematic.